The formulation of lactogenic banana flower biscuits (musa x paradisiaca abb) and its efficacy towards expressed breastmilk of lactating women - Zahariah Mohd Nordin (Kulliyyah of Allied Health Science, International Islamic University Malaysia, 2020)
Lack of breast milk production is the most frequent cause of breastfeeding failure in babies among lactating women. The uses of natural substances called galactagogue may assist the production of breast milk. Banana flower of plantain named Musa x paradisiaca ABB or locally known as Pisang Abu or Pisang Nipah contains galactagogue property which has been proven its effectiveness in an animal study. However, there is no data on its effectiveness on human yet. The aim of this study was to produce lactogenic biscuits made from banana flower of Pisang Abu or Pisang Nipah and to investigate the efficacy of the biscuits in increasing milk production within three weeks' consumption among lactating women. There are two phases of study. The first phase; the laboratory based experimental, involved the production process of banana flower into flour and biscuits, the sensory evaluation as well as proximate analysis. The banana flower flour was mixed with the wheat flour at a certain ratio to be prepared. Finally, four biscuits formulation were produced; as BFF30 (30% banana flower flour + 70% wheat flour), BFF40 (40% banana flower flour + 60% wheat flour), BFF50 (50% banana flower flour + 50% wheat flour) and BFF60 (60% banana flower flour + 40% wheat flour). All four formulated biscuits were analysed to determine their proximate nutrients and sensory acceptability. The best formulation was chosen as a prototype for the second phase experiment. In the second phase, a human trial was conducted among lactating working women. A total of 58 mother-infant pairs were assigned into two groups. Group I (n=29) consists of mothers who consumed plain biscuits as placebo while Group II (n=29) consumed the lactogenic biscuits which contained banana flower flour. Expressed breast milk, anthropometric indices of mothers and infants were recorded before and after the consumption of the biscuits. Dietary intake information of the respondents was taken to assess the maternal calories intake. The content of ash and fibre in the formulated biscuits were significantly (p<0.05) increased with the increased percentage of banana flower flour used whereby no significance difference (p>0.05) in terms of carbohydrate and fat content in all formulations. In terms of sensory evaluation, BFF50was the most acceptable formulation (p<0.05) and was chosen as the prototype. In second phase, the volume of expressed breast milk in experimental group (437.5±13.1 mL) after consuming lactogenic biscuits was significantly higher (p<0.05) compared to placebo group (377.384±13.1 mL). The secondary outcome which are the index of weight-for-age (6.76 ± 0.87 kg), height-for-age (0.64 ± 0.04 m); and BMI-for-age (16.45 ± 1.52 kg/m2) in Placebo group were not significantly different (p>0.05) compare to weight-for-age (6.81±1.01 kg), height-for-age (0.63 ± 0.04 M) and BMI-for-age (17.15 ± 1.40 kg/m2) in infants of experimental group after the intervention. In conclusion, the consumption of lactogenic biscuits in lactating mothers help to increase the expressed breast milk without any adverse effect. However, even though the second outcomes were not significantly different to placebo, each anthropometry indices showed that all infants were in normal growth. This study successfully showed that banana flower biscuit can induce the production of expressed breast milk among lactating women